Efficacy and Safety of a Biweekly Viscosupplementation Regimen for Knee Osteoarthritis - Yiasemidou, Marina; Munir, Usama; Glassman, Daniel; Teanby, David (The Journal of Knee Surgery, 2016)
Osteoarthritis is the most common form of arthritis in the Western world, causing disabling symptoms in 10% of people older than 55 years. Hyaluronic acid injections can reduce osteoarthritic pain but require three to five doses administered weekly. This preliminary study aims to assess the efficacy of a more flexible viscosupplementation regimen. Patients were given three sodium hyaluronate isotonic solution injections (Ostenil; TRB Chemedica SA, Vouvry, Switzerland), biweekly. They were then asked to record their pain before and after administration of the injections, on a visual analog score. A total of 91 knees were injected. Analysis of the data showed that the viscosupplementation injections significantly reduced the baseline pain within the first 24 to 48 hours post first injection (before injection, 68.8mm; 2 days postinjection, 48.9 mm; p < 0.001); these effects were maintained up to 6 months. No adverse effects were reported. The proposed regimen appears safe and efficient in reducing osteoarthritic pain of the knee joint. A randomized controlled study is needed to confirm these results.
Keywords: knee osteoarthritis; viscosupplementation; pain control